ORGANIZATIONAL PERFORMANCE: IDENTIFYING COMPETENT HUMAN RESOURCE CRITERIA - Rohani, Azmi; Suratman, Robiah; Idrus, Durrishah (International Journal of Psychosocial Rehabilitation, 2020)
Organizational performance is a collective effort of different people that are working together in realising the target goals. Determinants of organizational performance are tracked and measured in multiple dimensions depending on the environment and purpose of the organization. Besides the fact that organizational performance is measured by output and any other managerial factor, human resource is the key element in animating the process of organizational service and production. In working towards and attaining a beneficial outcome or improvement, most of the organizations, whether it is a public or private sector has introduced assessment techniques that provide the mechanism for measuring and evaluating the human resource factors to evaluate progress or impact. Human Resource Development Strategies act as a strategic plan in providing more competent employees that will contribute to improvements in organizational performance. Accordingly, this article adopts a content analysis approach by reviewing previous research on human resource development strategies. This paper highlights three competency criteria in human resource which are: attitude and behaviour, intellectual, and experience. The findings are beneficial for organizations in training employees to be competent because good employees are assets for organizations.